2009
DOI: 10.1186/1471-2350-10-17
|View full text |Cite
|
Sign up to set email alerts
|

Studies of CTNNBL1 and FDFT1variants and measures of obesity: analyses of quantitative traits and case-control studies in 18,014 Danes

Abstract: Background: A genome-wide scan in unrelated US Caucasians identified rs7001819 upstream of farnesyl-diphosphate farnesyltransferase 1 (FDFT1) and multiple variants within catenin (cadherinassociated protein), β-like 1 (CTNNBL1) to associate strongly with body mass index (BMI). The most significantly associating variants within CTNNBL1 including rs6013029 and rs6020846 were additionally confirmed to associate with morbid obesity in a French Caucasian case-control sample. The aim of this study was to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
2
9
0
1
Order By: Relevance
“…Liu et al 92 used directly measured fat mass as a control on the BMI analyses, but did not control for effects of body size on fat mass, and so both phenotypes contain information about nonfat body compartments. Consistent with this potential confounding, the replication study by Andreasen et al 94 found no association with BMI, but significant associations with weight and height. CTNNBL1 variants may be associated with increased risk of obesity, but the measured effect size on BMI includes an unknown but probably substantial contribution from genetic effects on body size.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Liu et al 92 used directly measured fat mass as a control on the BMI analyses, but did not control for effects of body size on fat mass, and so both phenotypes contain information about nonfat body compartments. Consistent with this potential confounding, the replication study by Andreasen et al 94 found no association with BMI, but significant associations with weight and height. CTNNBL1 variants may be associated with increased risk of obesity, but the measured effect size on BMI includes an unknown but probably substantial contribution from genetic effects on body size.…”
supporting
confidence: 72%
“…CTNNBL1: multiple SNPs mainly in intronic regions of CTNNBL1 were associated with BMI and fat mass in a sample of unrelated US Caucasians and were supported in a French Caucasian case-control study of categorical obesity, 92 but not in a central European sample 93 or a Danish sample. 94 Failure of replication is an expected feature of a heterogenetic model in which different populations or smaller groups (down to families) could be expected to have different genetic origins of obesity susceptibility. The effect size of 2.7 kg/m 2 would be detectable in a reasonably powered linkage study, but there are reasons to doubt the specificity of the continuous phenotypes for body fatness.…”
mentioning
confidence: 99%
“…Amphibians are highly philopatric, which reduces gene flow and produces large genetic differentiation between subpopulations (e.g., Beebee, 2005; Cushman, 2006; Funk, Blouin, et al. 2005; Murphy, Evans, & Storfer, 2010; Zhan, Li, & Fu, 2009). They also have strict environmental requirements, and movement away from their natal habitats may make them vulnerable to conditions that do not fit in their narrow survival spectrum (Murphy et al., 2010; Stebbins & Cohen, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhan et al. (2009) failed to detect a significant barrier effect of the Tsinling Mountains, a major divider in the continental East Asia landscape, to Chinese wood frogs ( Rana chensinensis ). Mountain ranges are often perceived as major genetic barriers to amphibian species, and Zhan et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation